“Cold and luminous act of cold and numinous faith”: Magdalena Chocanos’s Poetry - Usandizaga, Helena (Anales de Literatura Hispanoamericana, 2009)
This work presents the poetry of Magdalena Chocano (Lima, 1957) from some mechanisms of reading in an analysis that strives to open a dialogue about this sparsely distributed work, however rich in intensity and exceptional quality.First, the poetic subject is analyzed from beyond a generic definition in order to study the forces and wisdom at play that it produces as well as the creation of a place of observation from where the poem is generated and enunciated. The idea is to go beyond stereotypes and counter-stereotypes by taking note of the re-reading of feminine figures of history and the interactive construction of consciousness.This work also takes an in-depth look at how this self-ironic and unconventional poetic voice projects knowledge into a poetry that is the result of tensions between opposing forces but also creates a paradoxical and precarious faith building as a simulacrum in the poem. This acts in an imaginative and even subversive way and creates a tension with the power that makes these poems appear to be a discourse built beyond the establishment.
Keywords: Contemporary peruvian poetry; Poetic subject; Magdalena Chocano